PERANCANGAN KARAKTER IP 3D YANG MENGADAPTASI SATWA BADAK JAWA UNTUK USIA 18-25 TAHUN - Hanif Al Ihsan; Sultan Arif Rahmadianto; Ayyub Anshari Sukmaraga (Ma Chung Press, Universitas Ma Chung, 2026)
This final project focuses on the design of a 3D character IP inspired by the Javan Rhino, one of Indonesia’s critically endangered species. The goal of this project is to raise awareness of wildlife conservation among the younger generation (ages 18–25) through an engaging and meaningful visual medium. The research methodology combines literature study, comparative analysis, and questionnaires to gather data of the target audience and their perception of fictional animal-based characters. Based on these findings, a biomechanical character named